UPAYA PENGELOLA USAHA PEMBUATAN TEMPE LELA JAYA DALAM MENINGKATKAN KUALITAS PRODUK - Fera Sari; Agus Zainal Ramat; Suardi Jasma (UNIB Press, Universitas Bengkulu, 2019)
The perpose of thi is research is to know the effort of management manufarturing business lela jaya tempe at home industry to increase family economi in manna south bengkulu. The is research lising quatitative reseach metode. To guarintee the validity of data. The researcher take triagulation of researcher subject and collecting data technique. Based on the research goal and the discussion can be concloded 1) in the improving a product guaity there are same that should be considorod, starting from row material selections production process until the packaging. Which are the row materias that hase ehoorod is a good row materials and prioritizing taste to make a good product and can fullfilling costumer needed. 2) merketing strategy of the product according to needed and desire of target marker. Aso give the sahsfadon of the coshimer. The manager of tempe lela jaya used marketing techic koitc obseroe kargot market needed by selling the product to restourant, vegetable shop, greengrocer and fried food seller. Which are in Manna Bengkulu Selatan and product quality guarantee the manager aso give not risk to the seller. The most important is the satifaction of the costomeri. 3) financial anaysis that used bby the manager of tempe tela jaya business is a simple entry which us used to nolice all of income and oatcome to know disadoentages or aduentager that obtained by the business. 4) the obstacles is weather conditions beside at the thing that can be manager support easy acces to get the material and easly production process. Keywords : product quality, strategy